KAJIAN MORFOLOGI KOSAKATA DALAM BENTUK VARIASI BAHASA SLANG KOMUNITAS TRANSGENDER DI SURABAYA: KAJIAN MORFOLOGI KOSAKATA DALAM BENTUK VARIASI BAHASA SLANG KOMUNITAS TRANSGENDER DI SURABAYA - Cahyo Prawoto, Eko; Akbar, Amiruddin (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2022)
Variations in slang are variations of the language used by a particular community in which the language variation is only known and understood by certain communities, for example the transgender community in Surabaya. To find out the meaning of the slang variation of the transgender community, a method can be used, namely by looking at the morphological formation process of a vocabulary variation of the slang language variation of the transgender community. In the morphological process, there is a theory that has been found by previous researchers in relevant research, namely the classification of five forms of community slang variations. Based on the results of previous relevant studies, the researchers found an advanced theory which aims to make it easier to determine the morphological process. The method used by the researcher is the method of observation and interviews with resource persons in the transgender community in Surabaya. The result of this research is that the researcher finds advanced theory in the categorization of forms of slang variations. The two categories are specifically and categories in general.